Hospital morbidity pattern in children under 1 year of age born in Sheffield 1975-6. Issue 1 (January 1981) - Lloyd, B; Pursall, E; Emery, J L
Abstract : The morbidity pattern, based on hospital admissions for a complete year's cohort of all children born in Sheffield 1975-6, was studied. In many children the diagnosis given on admission had changed by the time they were discharged from hospital. About one-quarter of children under age 6 months were admitted for social reasons. Despite a decreasing birth rate the admission rate had increased, with an overall admission rate of 11.2% of all births. The rates and ages at which children are admitted varied greatly according to the month of birth. This is an important factor if cohort studies from different places are being compared.